Dual Disadvantage: An Examination of Racial Disparities in Victim and Suspect Criminal Justice Treatment - Vaughn, Paige (2020)
During the past several decades, American criminal justice legal systems appear to have been over-punishing Black individuals as perpetrators of crime, and neglecting them as violent crime victims, perpetuating disparities that simultaneously repress and alienate Black citizens. Such complex processes of racial inequality are difficult to capture in studies that focus on single criminal justice stages and limited sets of variables. After presenting a working conceptualization of case processing that can be used across criminal justice systems, the current study uses data from the St. Louis Metropolitan Police Department, St. Louis Circuit Attorney’s Office, and U.S. Census to assess racial disparities in victim and suspect treatment across police clearance and prosecutorial case screening stages. The results demonstrate that the effects of race and other case-level characteristics largely depend on the criminal justice stage in question, as well as the inclusion of victim and suspect race – and their interaction – in models. Importantly, the findings suggest that racial disparities in criminal justice system treatment may be experienced during initial criminal justice stages. Situating studies of case processing within a general framework that examines the different effects of victim and suspect race is key in pointing to racial disparities and discerning the theoretical mechanisms underlying criminal justice system treatment. Future research should continue studying racial disparities in clearance and case screening, and should connect these early stages of case processing to later ones